Field-resolved, far-field characterization of air bubbles in liquid water - Srivastava, A.; Herbst, A.; Fattahi, H. (2024 IEEE Photonics Conference, IPC 2024 - Proceedings, 2024)
Field-resolved spectroscopy at near-petahertz frequency, femtosecond fieldoscopy, is emerging as a powerful technique for investigating resonance constituents of samples in aqueous environments or soft matter. We report on self-referencing and label-free identification and classification of samples with refractive index disparities by far-field femtosecond fieldoscopy with attosecond precision.
CRIS-Team Scopus Importer:2025-02-04
Keywords: femtosecond fieldoscopy; field-resolved spectroscopy; refractive index measurement; ultrafast spectroscopy